DEGREES AND CLINICAL DESCRIPTION OF MENTAL RETARDATION - Kahramonova Zebuniso Raufjonovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This article provides information on the degrees and clinical description of dementia. Mentally retarded refers to a steady decline in mental, primarily intellectual development as a result of organic damage to the brain.